Development of integrated pest management “perosak & penyakit” app with economic threshold and pesticide mode of action to assist Malaysian rice farmer decision making - Mazlan, Norida; Ismail, Mohd Razi; Che'ya, Nik Norasma; Chee, Leong Khong (International Society for Southeast Asian Agricultural Sciences, 2024)
The Integrated Pest Management (IPM) is a globally recognize sustainable approach for pest management in farm. The IPM integrates regular pest monitoring, cultural and biological controls, and prudent pesticide use at Economic Threshold Levels (ETL). In management of rice pest, various factors such as type of pest, suitable control methods and types of pesticides are sometimes become too much for farmer’s process. The use of mobile application (app) could help the farmer for making decision. However, local farmers encounter barriers accessing Malay language smartphone apps offering IPMbased information on rice pest and disease management. Thus, this study sought to develop an app providing such information in Malay, based on IPM approaches. A database was compiled with details on managing 18 rice pests and 14 diseases, including basic information, symptom descriptions with relevant photos, and IPM-based control methods. In November 2020, an Android prototype was developed using offline mobile app architecture. Subsequent testing confirmed the prototype adhered fully to design and database specifications. In December 2020, a re- test involving 13 farmers and 11 agricultural officers was conducted, gauging perceptions of ease of use, interface satisfaction, and usefulness. The median scores for these domains were 6.000 (IQR: 1.3000), 6.1875 (IQR: 1.0625), and 6.0833 (IQR: 1.2083) respectively. Generally, a new Malay language app - 'Perosak & Penyakit Padi' has been successfully developed with the intention of aiding local farmers in making decisions regarding insecticide application for rice insect pest management.